Implementation of the Electronic-Based Government Administration Policy in Selamanik Village, Cipaku District, Ciamis Regency - Mira Dwi Kuswandani; R.Rindu Garvera; Neti Sunarti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This research is motivated by the fact that e-government implementation in Selamanik Village, Cipaku District, Ciamis Regency has not been running optimally. The purpose of this study is to determine the implementation of e-government policies in Selamanik Village, Cipaku District, Ciamis Regency. The method used in this study is a qualitative approach. Seven informants were recruited. Data collection techniques included literature review, fieldwork (observation and interviews), and documentation. The author used qualitative data analysis techniques through processing interview and observation data to draw conclusions that can answer the research questions. Based on the research results, it is known that: The implementation of the e-government policy in Selamanik Village, Cipaku District, Ciamis Regency has been carried out fairly well, but not yet fully optimal. This is evident in the village government's commitment to implementing e-government through digital public service delivery, community outreach, ongoing information delivery, service procedures and Standard Operating Procedures (SOPs), and the division of village officials' duties according to their respective core duties and functions. Therefore, the successful implementation of e-government policies in Selamanik Village requires ongoing efforts, including capacity building for village officials, strengthening information and communication technology infrastructure, and increasing community participation and digital literacy to optimally achieve the goals of e-government.Keywords: Implementation, Policy, E-Government